China as a leader of the world economy - Chow, Gregory C., 1929- (Singapore ; Hackensack, N. J. : World Scientific, 2012)
'After the 1978 economic reform, China's economic development has been on a fast track ever since. Later on, the successful accession into the WTO in 2001 accelerated China's economic transformation and made it more integrated with the world. Today, as the second-largest economy in the world, China has earned herself a leading role on the world stage beyond dispute. This book provides readers with answers to why and how China functions as a leader in the world economy. The book surveys China's economy in four parts--economic institutions, economic problems, important economic policies and selective economic analysis, especially including many hot issues like revaluation of the reminbi, China's high inflation rate and its relations with other emerging markets, etc.'--Publisher's description.
Introduction : an overview of China's economy -- Three important players of China's economy -- Is Chinese capitalism different? -- Economic planning in China -- Role of economists in China's economic development -- Free to choose in China -- Chinese and American economic institutions reflecting cultural differences -- Outflow of capital and China's diplomacy -- Brazil and China as economic partners -- India's model of rapid economic development -- Will the Russian economy grow rapidly? -- Comparing economic developments in Taiwan and mainland China -- Problems facing the Chinese economy -- Directions for economics education and research in China -- Important lessons from studying the Chinese economy -- US housing bubble and economic downturn -- Will consumption expenditures in China increase rapidly? -- From Guangzhou's opera house to issues of economic development -- Lessons from the current American great recession -- How to improve university education in China? -- How to manage a university well? -- How to improve the efficiency of state enterprises? -- Carry out the open door policy further -- How to stop inflation in China? -- How to solve the problems of China's inflation and the American recession? -- China's aging population -- China's environmental policy : a critical survey -- Note on a model of Chinese national income determination -- Lessons from studying a simple macroeconomic model for China -- Shanghai stock price movements reflecting China's globalization -- Co-movements of Shanghai and New York stock prices by time-varying regressions.
Includes bibliographical references and index.
Keywords: International economic relations; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-; China -- Foreign economic relations